2004
DOI: 10.1152/ajpcell.00300.2004
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein regulates apoptosis in lung cancer cells through protein kinase A

Abstract: Parathyroid hormone-related protein (PTHrP)-(1–34) and PTHrP-(140–173) protect lung cancer cells from apoptosis after ultraviolet (UV) irradiation. This study evaluated upstream signaling in PTHrP-mediated alteration of lung cancer cell sensitivity to apoptosis. The two peptides increased cAMP levels in BEN lung cancer cells by 15–35% in a dose-dependent fashion, suggesting signaling through protein kinase A (PKA). In line with this view, the PKA inhibitor H89 abrogated the protective effects of PTHrP-(1–34) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…It was reported that Pthrp inhibits apoptosis in cartilage (Yamanaka et al . 2003) and in lung tumors (Hastings et al . 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that Pthrp inhibits apoptosis in cartilage (Yamanaka et al . 2003) and in lung tumors (Hastings et al . 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since PTH1R stimulates cAMP as its second messenger in H1944 cells (Hastings et al 2009) and BEN lung cancer cells (Hastings et al 2004; Kukreja et al 1988; Pizurki et al 1988), we investigated the direct effects of cell-permeant cAMP compounds on H1944 cell growth. 8-CPT-cAMP, a non-selective analog, inhibited the rise in cell number in a time- and dose-dependent manner (Figure 2a, b).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that PTH1R activation was coupled to Gs and generation of cAMP in H1944 cells and BEN lung cancer cells, rather than Gq pathways (Hastings et al 1996, 2004, 2009). When cell-permeant cAMP analogs were tested in this study, they mimicked the effect of PTHrP in inhibiting H1944 cell growth.…”
Section: Discussionmentioning
confidence: 98%
“…However, the effect of the Gαs–cAMP signaling system on apoptosis was different among lung cancer cells. The Gαs–cAMP signaling system protects lung cancer cells from ultraviolet radiation‐induced apoptosis ( 28 ) and plays an important role in cell growth and survival of H1734 non‐small cell lung cancer cells. ( 29 ) Therefore, it is essential to investigate the mechanisms that determine the effects of the cAMP signaling system on the cell death of lung cancer cells for the development of a new strategy to increase the therapeutic effect of cytotoxic drugs or radiation by modifying the cAMP signaling system.…”
Section: Discussionmentioning
confidence: 99%